Psychedelic Therapies at the Crossroads of Trauma and Substance Use: Historical Perspectives and Future Directions, Taking a Lead From New Mexico - Bhatt, Snehal R.; Armstrong, Maya; Parker, Tassy; Maviglia, Marcello; Kass, Rebecca; Leeman, Lawrence; Romo, Paul; Ziedonis, Douglas (Frontiers in Pharmacology, 2022)
Post-traumatic stress disorder (PTSD), a common condition with potentially devastating individual, family, and societal consequences, is highly associated with substance use disorders (SUDs). The association between PTSD and SUD is complex and may involve adverse childhood experiences (ACEs), historical and multi-generational traumas, and social determinants of health as well as cultural and spiritual contexts. Current psychosocial and pharmacological treatments for PTSD are only modestly effective, and there is a need for more research on therapeutic interventions for co-occurring PTSD and SUD, including whether to provide integrated or sequential treatments. There is a current resurgence of interest in psychedelics as potential treatment augmentation for PTSD and SUDs with an appreciation of the risks in this target population. This paper reviews the historical perspective of psychedelic research and practices, as well as the intersection of historical trauma, ACEs, PTSD, and SUDs through the lens of New Mexico. New Mexico is a state with high populations of Indigenous and Hispanic peoples as well as high rates of trauma, PTSD, and SUDs. Researchers in New Mexico have been leaders in psychedelic research. Future directions for psychedelic researchers to consider are discussed, including the importance of community-based participatory approaches that are more inclusive and respectful of Indigenous and other minority communities.